Robust localization over obstructed interferences for inbuilding wireless applications - Kong, Youngbae; Kwon, Younggoo; Park, Gwitae (IEEE transactions on consumer electronics, 2009)
Location-awareness can be applied to the various consumer applications. A received signal strength (RSS) based localization system is relatively inexpensive and simple to be implemented without additional hardware supports. However, the radio signals are strongly affected by the obstructed interferences. This is a difficult problem for the RSS based localization systems to be implemented in real world. To solve this problem, we propose a practical and robust localization algorithm in the obstructed environments. The proposed algorithm uses the Maximum Likelihood Estimation (MLE) based on the position probability grid. In addition, the proposed algorithm detects and compensates the large measurement error using the Min-Max algorithm. We evaluated the performance of the proposed algorithm in the obstructed environments. Performance results show that the proposed algorithm outperforms other algorithms on the obstructed environments.